2016
DOI: 10.3390/nu8100625
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Trans Fatty Acids in Children Aged 4–5 in Spain: The INMA Cohort Study

Abstract: Trans fatty acid (TFA) intake has been identified as a health hazard in adults, but data on preschool children are scarce. We analyzed the data from the Spanish INMA Project to determine the intake of total, industrial and natural TFA, their main sources and the associated socio-demographic and lifestyle factors in children aged 4–5 (n = 1793). TFA intake was estimated using a validated Food Frequency Questionnaire, and multiple linear regression was used to explore associated factors. The mean daily intakes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The consumption of TFA by Tunisian children was very low compared to data registered elsewhere. Monge-Rojas et al (2013) reported a mean TFA intake of 1.3% E in Costa Rican adolescents [ 30 ], while the average dietary intake of TFA in Spanish children aged 4–5 years old was 1.36 g/d which corresponds to 0.77% E [ 31 ]. Results from Canadian children aged 5–6 years old showed a mean TFA intake of 0.71% E [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of TFA by Tunisian children was very low compared to data registered elsewhere. Monge-Rojas et al (2013) reported a mean TFA intake of 1.3% E in Costa Rican adolescents [ 30 ], while the average dietary intake of TFA in Spanish children aged 4–5 years old was 1.36 g/d which corresponds to 0.77% E [ 31 ]. Results from Canadian children aged 5–6 years old showed a mean TFA intake of 0.71% E [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Costa Rica, bakery products, red meat and dairy products were the main contributors to SFA and TFA intakes in adolescents [ 30 ], while fried eggs, whole milk, breakfast cereals and fresh cheese were among the major food sources of total fat and SFA in diets of Guatemalan schoolchildren [ 27 ]. The principal food groups contributing to the total TFA intake in Spanish children were milk (21%), processed baked goods (16%), sweets (12%), fast food (12%) and white bread (10%) [ 31 ]. These were comparable to those reported in the Canadian study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most other NEFA, TFA are derived exclusively from the diet. Most ingested TFA are generated during industrial processing of vegetable oils rich in PUFA through partial hydrogenation [22], though some comes from milk ingestion [23]. TFA inside cells alter membrane properties and lead to endoplasmic reticulum stress, reactive oxygen species, inflammation, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[2013] reported mean TFA intake of 1.3 % E in Costa Rican adolescents (28) , while the average dietary intake of TFA in Spanish children aged 4-5 y was 1.36 g/d which corresponds to 0.77 % E (29) . because the overall levels of TFA in most processed food products available on the Tunisian market are low (<1 g/100g of sample), except in margarine (5.56 g/100g).…”
Section: Discussionmentioning
confidence: 99%